Избранная лирика - Гарсиа Лорка Федерико (Избранная зарубежная лирика, 1975)
Экземпляры: КХ (20150327) / Инвентарный номер: 0224309 / Цена: 0.06 / Сис.шифр: И(Исп) / Авт.знак: Г 21 / ГРНТИ: 17 / ББК: 84(4/8)